Risk management framework for the delivery of public-private partnership (ppp) housing construction project : case study of malaysia housing programme (pr1ma) - Putri Zulaiha, Razi (2020)
In many developing countries, Public-Private Partnership (PPP) has shown an increased reliance not only for infrastructure development but it has expanded in other sectors that including social housing (affordable houses). However, there are evident in previous literature on the accounts of lacking success reporting on the PPP housing approach, plus inadequacy of proper evaluation for PPP performance projects. This study aims to develop a risk management framework based upon the derived risk index determined by the analysis of quantitative Analytical Hierarchy Process (AHP), used as an indicator for the project performance score. This study is designed in three (3) phases by employing a mixed-method approach (qualitative and quantitative). Results demonstrated that a total 9 risk elements and 33 sub-elements obtained from the literature review and was validated during pilot study, by employing semi-structured interview, with eight (8) PPP housing construction experts. The data set for the study comprised thirty-three (33) construction experts involved in the PPP housing construction project. Results showed that natural hazard risk (geologic hazard risk) and economic and financial risk (inflation and interest rate) risk prevails as extreme external risks that influenced PPP housing project performance more than the market and social-politics risk. On the contrary, unreliable value for money and fluctuation in the currency exchange rate of economic and financial risks discovered as moderately influenced PPP housing project performance. Similarly, project-related risk (internal) in procurement and contractual risks that including (absence of transparency and accountability during the procurement process, and absence of a robust and clear agreement) discovered will moderately affect the delivery of PPP housing project performance risks. Akin in moderating the effect in technical faulty risks are (unforeseen ground condition and shortage of technical expertise). Eventually, it was found that internal risks monopolized the low risks occupied within the risk index of (0.000 < RI ≤ 0.050) including insufficient capacity in procurement and negotiation, frequent design change, design over-specification, poor quality workmanship, absence of specific PPP framework and inadequate PPP skills and knowledge leading to poor planning. While captured from external risks are financial incapacity of private partners, weak state intervention, and persistent land acquisition. Risk response strategy for the extreme risks categorized within (0.100 < RI ≤ 0.150) is by avoiding the risk and best to assign the risks to the private sector. On the contrary, risk response approaches suggested considering the medium risks categorized at interval (0.050 < RI ≤ 0.100), is to transfer the risks and shared within both parties, i.e. public and private. While for low risks lies between (0.000 < RI ≤ 0.050), all the risks best to accept and retained within the public sectors. Taken together, the development of risk response and risk mitigation plan that emerged from the risk index offered significant contribution which has gain a new understanding that risks with severe or low exposure can be reduced or avoided taking into account its strategic and effective response and mitigation approaches. The developed risk management framework is expected to assist the successful implementation of risk management for the PPP housing project and the success of the PPP housing project.